Lutein administration to pregnant women with gestational diabetes mellitus is associated to a decrease of oxidative stress in newborns. (28th June 2013) - Lorenzoni, Francesca; Giampietri, Matteo; Ferri, Giulia; Lunardi, Sara; Madrigali, Valeria; Battini, Lorella; Boldrini, Antonio; Ghirri, Paolo
Abstract: Oxidative stress (OS) is defined as an imbalance between pro- and antioxidant factors that can lead to cellular and tissue damage. Under condition of gestational diabetes, OS is exacerbated and can cause vascular dysfunction in the placenta, leading to fetal and perinatal complications. We investigated the oxidative status of diabetic pregnant women and of their babies. A group of those diabetic women received lutein, and another group did not receive anything. In order to verify a possible antioxidant function of lutein, we compared the OS values of the two groups. OS appeared lower in treated gravidas than in untreated ones; however, there was not a statistically significant difference between the two groups. As far as newborns are concerned, there was a significant difference of OS values between babies born to mothers treated with lutein and newborns to mothers untreated at 2 h of life. However, at 48 h, there was not a significant difference between the two groups. In conclusion, lutein administration during pregnancy significantly reduced neonatal OS at birth. Further studies are necessary to evaluate the effects of combined administration to mother and infants.